Delayed Small Bowel Ischemia following Minor Mesenteric Injury - Gil Hwan Kim; Jae Hun Kim; Sang Bong Lee (Journal of Acute Care Surgery, 2019)
We report a case of delayed presentation of small bowel ischemia following minor mesenteric injury after blunt abdominal trauma. Traumatic small bowel and/or mesenteric injury is rare, and minor mesenteric injury is usually managed conservatively. However, mesenteric injury may cause potentially fatal conditions such as hemorrhages or peritonitis in extremely rare cases and require laparotomy. We present a case of small bowel ischemia that occurred 3 days after minor mesenteric injury from blunt abdominal trauma.